The role of agriculture in poverty reduction in Pakistan: proceedings of a seminar organized by the International Food Policy Research Institute and Beaconhouse National University with assistance from Innovative Development Strategies (Pvt.) Ltd.. March 12, 2005. Lahore, Pakistan. - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
This volume represents the outcome of a joint effort by IFPRI and Beaconhouse National University, Lahore, with support from the Institute of Development Studies (IDS), to bring together some of the brightest and most influential minds in academia and policymaking circles to discuss the role of agriculture in poverty reduction in Pakistan. A day-long seminar took place on March 12, 2005 in Lahore, Pakistan. The seminar focused on four issues: analysis of the causes of and solutions to rising poverty trends, overview of key agricultural issues in Pakistan, examination of prospects for rural industrialization, and evaluation of Pakistan’s progress in achieving the Millennium Development Goals. Rich and stimulating presentations were followed by lively and wide-ranging discussions. Over 120 participants, representing the academic, policymaking, and donor communities, along with students, representatives of civil society, and the media, attended this event.